Accounting standards compliance and comparability of measurement practices: the case of Malaysian general insurers - Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar (Universiti Utara Malaysia, 1999)
This study determines the extent of compliance level of Malaysian general insurers towards the requirements stipulated in MAS 3 (Malaysian Accounting Standard No. 3 Accounting for General Insurance Business) and GPI (Guidelines on Accounting for Insurance Business, JPI/GPI 3), and subsequently determines the comparability of relevant measurement practice outlined in the Standards and Guidelines. Data from the annual reports of 35 insurers were gathered 18 measurement practices were examined in the study. The Herfindahl index (known as H-index) was employed in measuring the comparability of measurement practices. Except for the accrual of dividends, results suggest that the compliance level of companies towards most of the other items were high. Nevertheless, results on comparability of measurement practices were rather mixed, having H-indices ranging from a low score of 0.47 to a prefect score of 1.